2010
DOI: 10.1007/s11104-010-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing P status and P requirement of tea (Camellia sinensis L.) by leaf and soil analysis

Abstract: In this paper we present a new method for evaluating soil and plant tests for phosphate (P). We apply it to field experiments conducted over 2 years in four widely separated tea gardens of the Terai and the Dooars regions at the Himalayan foothills of India. We applied 5 levels of P to each site and measured yield, P concentration in the leaves, and Bray P values through time. Leaf P concentrations were closely described by a 3-dimensional Mitscherlich equation in which one of the independent variables was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The leaf N concentration was determined using the micro-Kjeldahl method with a nitrogen determinator (Kjeltec™ 8000, FOSS Group, Hiller, Denmark) [19]. The total leaf P concentrations were measured with a molybdate/stannous chloride method with an ultraviolet spectrophotometer (Lambda750, PerkinElmer Inc., Waltham, MA, USA) [20]. The leaf K concentrations were determined by atomic absorption spectrometry with an atomic absorption spectrophotometer (AA-240, Varian Inc., Palo Alto, CA, USA) [21].…”
Section: Leaf Nutrients and Chlorophyll Contentmentioning
confidence: 99%
“…The leaf N concentration was determined using the micro-Kjeldahl method with a nitrogen determinator (Kjeltec™ 8000, FOSS Group, Hiller, Denmark) [19]. The total leaf P concentrations were measured with a molybdate/stannous chloride method with an ultraviolet spectrophotometer (Lambda750, PerkinElmer Inc., Waltham, MA, USA) [20]. The leaf K concentrations were determined by atomic absorption spectrometry with an atomic absorption spectrophotometer (AA-240, Varian Inc., Palo Alto, CA, USA) [21].…”
Section: Leaf Nutrients and Chlorophyll Contentmentioning
confidence: 99%
“…Previous studies have well reported the cycle of individual elements, such as Al (Flaten 2002), N (Han et al 2012) and P (Debnath et al 2011) in tea plantations, which were generally tested by our study. However, we know little about at what points the major biogeochemical cycles interact and how these linkages are affected by environmental change and fertilization management and the development of tea plantations (Marklein and Houlton 2012).…”
Section: Discussionmentioning
confidence: 87%
“…The interplay between aluminum (Al) and nutrients in tea (Camellia sinensis L.) plantations is of scientific and social interest (Ruan et al 2006) since (1) tea plants are an Al-accumulating shrub (Dong et al 2001;Tolrà et al 2011) and commercially available tea contains large amounts of Al. A further 30-40% of Al could be absorbed into infusions and thus absorbed by tea drinkers (Flaten 2002); (2) a potential link between high Al contents in tissues and various neuro-degenerative disorders such as Alzheimer's disease has been reported (Nayak 2002); (3) soil pH and nutrients have been altered by atmospheric deposition with global environmental changes and fertilization due to productivity maintenance (Ruan et al 2000;Chen et al 2006;Wang et al 2010), this has affected the Al cycling in tea plantations (Fung and Wong 2002;Ruan et al 2004;Fung et al 2008;Duan et al 2012) and vice versa; for example, soil available Al promotes plants to absorb phosphate (Konishi et al 1985;Dong et al 2001;Debnath et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No correlation was found at all between extracted P and early dry matter yield, as the amount of extracted P is highly dependent on soil mineralogy and on the types of chemical bonding between P and soil inorganic and organic fractions. This complicates the use of soil testing for general analysis of fertilizer requirements ( Bell et al, 2005 ; Debnath et al, 2010 ). In other words, the plant availability of essential plant nutrients may often not be assessed through traditional soil testing methods as they cannot reflect the complex soil chemistry and rhizosphere effects involved.…”
Section: Soil Mineral Analysismentioning
confidence: 99%